Perspectives of the Open State in the Exponential Era, in Light of the Latin American Experience - Oszlak, Oscar (Revista del CLAD Reforma y Democracia, 2022)
As in the rest of the world, during the last decade Latin American States have been promoting various initiatives of “open government”, which recently reached parliaments and the courts, in a transition to an “open State”. This article reflects upon the prospects of these management philosophies becoming dominant paradigms of public governance in the region, in times of exponential changes characterizing the 4th Industrial Revolution, which pose new and complex challenges to state management. The emergence of open government is placed within the historical sequence of the successive paradigms that have dominated the field of public management, in order to find out the degree of continuity or rupture it implied vis-à-vis its predecessors. Then, it is examined the assumptions and challenges implicit in the adoption of its principles, as well as their modes of application. Finally, it is speculated about the perspectives of open government or open State becoming the threshold of typical way of governance of a deliberative democracy.